Sorption and transport of trichloroethylene in caliche soil - Akyol, Nihat Hakan; Yolcubal, Irfan; Yuksel, Derya Imer (Pergamon-Elsevier Science Ltd, 2011)
Sorption of TCE to the caliche soil exhibited linear isotherm at the high TCE concentrations (Co = 122-1300 mg L-1) but Freundlich isotherm at the low concentration range (1-122 mg L-1). Sorption strength of the carbonate fraction of the soil was about 100-fold lower than the sorption strength of soil organic matter (SUM) in the caliche soil, indicating weak affinity of TCE for the carbonate fraction of the soil. Desorption of TCE from the caliche soil was initially rapid (7.6 x 10(-4) s(-1)), then continued at a 100-fold slower rate (7.7 x 10(-6) s(-1)). Predominant calcium carbonate fraction of the soil (96%) was responsible for the fast desorption of TCE while the SUM fraction (0.97%) controlled the rate-limited desorption of TCE. Transport of TCE in the caliche soil was moderately retarded with respect to the water (R = 1.75-2.95). Flow interruption tests in the column experiments indicated that the rate-limited desorption of TCE controlled the non-ideal transport of TCE in the soil. Modeling studies showed that both linear and non-linear nonequilibrium transport models provided reasonably good match to the TCE breakthrough curves (r(2) = 0.95-0.98). Non-linear sorption had a negligible impact on both the breakthrough curve shape and the values of sorption kinetics parameters at the high TCE concentration (Co = 1300 mg L-1). However, rate-limited sorption/desorption processes dominated at this concentration. For the low TCE concentration case (110 mg L-1), in addition to the rate-limited sorption/desorption, contribution of the non-linear sorption to the values of sorption kinetics became fairly noticeable. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Trichloroethylene; Caliche soil; Sorption; Transport; Rate-limited desorption; Non-linear nonequilibrium